Actors in the Israeli-Palestinian conflict: Interests, narratives and the reciprocal effects of the occupation - Peter Lintl (Stiftung Wissenschaft und Politik (SWP), 2018)
The study examines the ways in which the Israeli-Palestinian conflict shapes and transforms the interests, narratives and options of relevant actors, in light of the failure of peace talks and the continuing occupation of the West Bank. The first contribution examines the Israeli discourse, laying out how the absence of resolution creates a paradoxical situation where majorities exist both for a two-state solution and against a Palestinian state. This translates politically into growing paralysis in relation to possible peace talks. The second contribution analyses how the Palestinian leaderships in Ramallah and Gaza City relate to the Israeli occupying power, within a spectrum of negotiations, resistance rhetoric and direct and indirect cooperation. The contribution also elaborates how the leaderships unintentionally became accessories to the occupying power. The third contribution explores how the EU's engagement suffers a discrepancy between stated objectives (two-state solution, Palestinian develop-ment) and achieved outcomes. It proposes concrete measures for resolving the conundrum. The fourth contribution examines the humanitarian organisation UNRWA, which operates under conditions of occupation and - inevitably but unwillingly - becomes a party to the conflict. The fifth and last contribution examines the Israel lobby in the United States. Whether the occupation of the West Bank lies in Israel's interests is found to be increasingly controversial among American Jews, and creating divisions within the Israel lobby.
Keywords: 320